Minor "dings" - major effects? a study into the cognitive effects of mild head injuries in high school rugby - Ackermann, Tessa Ruth (Rhodes University, Faculty of Humanities, Department of Psychology, 2000)
The present study is part of a larger and ongoing research initiative investigating the cumulative cognitive effects of mild head injury in rugby union and focused specifically on high school rugby players. A comprehensive battery of neuropsychological tests was administered to top team high school rugby players (n = 47), and a non-contact sport control group of top team high school hockey players (n = 34). Direct comparisons of group mean scores and standard deviations across each neuropsychological test were carried out for the Total Rugby group versus the Total Hockey group as well as for the subgroups Rugby Forwards versus Rugby Backs. A correlational analysis was conducted to ascertain whether a relationship exists between the number of mild head injuries reported by the players and their cognitive test performance. Results of the group comparisons of means and variability on WMS Paired Associate Learning Hard Pairs - Delayed Recall provides tentative indications of the initial stages of diffuse damage associated with mild head injury in the rugby group and provides some evidence for impairment of verbal learning and memory in the Rugby Forwards group. The correlational analysis revealed no significant relationship between number of reported mild head injuries and cognitive performance. The findings and possible latent effects of the multiple mild head injuries reported by the rugby players are discussed in terms of brain reserve capacity theory and suggestions for future research are provided.
Keywords: Rugby football injuries; Head -- Wounds and injuries -- Psychology; Head -- Wounds and injuries -- Complications; Head -- Wounds and injuries -- Patients -- Rehabilitation